Marine Gastropod Species Diversity in Rocky Intertidal Zone of Seri District, Ambon - Haumahu, Sara; Uneputty, Prulley A.; Natan, Yuliana (Agrikan Jurnal Agribisnis Perikanan, 2023)
Gastropoda diversities can be used as an ocean health index The higher the species diversity of marine gastropod s, the better the ocean environment. Recently, there is no publication on gastropod communities in the intertidal zone of Seri District, Ambon, Indonesia. The research on gastropoda communities was conducted in July 2023 at the intertidal zone of Seri district, Ambon. The objectives of the research were to identify the species of gastropods, to analyze its ecological density and abundance, and also to analyze gastropod diversity indices. Sampling was done at three sampling sites with simple random sampling method during low tide with applying sampling kuadrat about 5x5m. A total of 21 species of marine gastropod were found in this study which grouped into six ordo, 11 family and 16 genera. The higest number of species found in the ordo of Neogastropoda. Patelloida striata has the highest ecological density in station 1 and station 2 (7 individu.m-2 and 11 individu.m-2, respectively), whereas Patteloida saccarinoides and Nerita polita have the highest ecological density in station 2 (each has 8,47 individu.m-2). Shannon diversity index (H`) varied between 1,987 and 1,984. Pielou evenness index (J`) ranged from 0,656 to 0,903. Whereas Simpson dominance index (D) varied from 0,146 to 0,223. It can be concluded that gastropod species diversity in the intertidal zone of Seri District was categorized as low diversity, evenness index was moderate to higher, while there was no dominance species in the communities.